Sunday Star, 10 January 2010 - Shukry Mohd Salleh Datuk (Star Publications (Malaysia) Berhad, 2010)
Malaysia believes in providing balanced development to all citizens, This is to maintain social harmony and political stability.Only then can the economic fundamentals be attained and growth with balanced distribution achieved